Development of Orodispersible Films Containing Benzydamine Hydrochloride Using a Modified Solvent Casting Method - Pechová, Veronika; Gajdziok, Jan; Muselík, Jan; Vetchý, David (AAPS PharmSciTech, 2018)
The aim of this study was to develop benzydamine hydrochloride-loaded orodispersible films using the modification of a solvent casting method. An innovative approach was developed when the drying process of a small-scale production was used based on a heated inert base for casting the film. During this process, two types of film-forming maltodextrins for rapid drug delivery were used. They were plasticized with two different polyols (xylitol and sorbitol). Superdisintegrant Kollidon® CL-F was tested as an excipient that can induce faster disintegration of the prepared films. The influence of the formulation parameters (dextrose equivalent of film-forming maltodextrins, a type of plasticizer, and the presence of superdisintegrant) on the disintegration time, mechanical properties, and moisture content of films was statistically evaluated using a multivariate data analysis. Orodispersible films containing maltodextrin with lower dextrose equivalent value showed better mechanical properties (tensile strength ranged from 886.6 ± 30.2 to 1484.2 ± 226.9 N cm-2), lower moisture content (0.5 ± 0.0 to 1.2 ± 0.2%), and shorter disintegration time (17.6 ± 2.9 to 27.8 ± 2.8 s). Films plasticized with xylitol showed shorter disintegration time (17.6 ± 2.9 to 29.2 ± 3.8 s) than films containing sorbitol (23.8 ± 2.9 to 31.7 ± 3.9 s). With the addition of superdisintegrant Kollidon® CL-F, a significant influence on disintegration time was not observed. The modified solvent casting method shows great promise in a small-scale laboratory production of orodispersible films, e.g., in a pharmacy lab.
Keywords: benzydamin; Polysaccharides; lékové transportní systémy; Solvents; solvent casting method; změkčovadla; polysacharidy; multivariate data analysis; orodispersible films; maltodextrins; povidon; Drug Delivery Systems; benzydamine hydrochloride; rozpouštědla; Povidone; Benzydamine; Plasticizers